Pengaruh Perawatan Metode Kanguru Terhadap Respon Fisiologis Bayi Berat lahir Rendah - Rahayu Catur Ria Wati; Risa Etika; Esti Yunitasari (Pediomaternal Nursing Journal, 2019)
Introduction: Low Birth Weight Babies (LBWB) is one of the causes of the high Neonatal Mortality Rate in Indonesia. This occurs because LBWB has non-optimal temperature regulation centers, thin-brown and subcutaneous fat tissue, inadequate muscle growth, and organ immaturity. Kangaroo Care (KC) is expected to be an effective and efficient solution to keep LBW in a stable condition. This study aimed to determine the effect of KC on the physiological responses of LBWB.Methods: This study is a pre-experimental design with one group pretest-posttest research design. The sample was obtained with a total sampling technique and the size was 21 LBWB. The independent variable in this study was KC; carried out for 3 days with a frequency of 2 times a day and 90 minutes per KC. Meanwhile, the dependent variable was the physiological responses of LBWB which consisted of temperature, heart rate, and oxygen saturation. The instrument used was KC observation sheets with Wilcoxon signed rank test for the data analysis.Results: The study showed that the temperature increased from 36.50C to 36.90C; the heart rate increased from 135 x/minute to 147 x/minute; the oxygen saturation increased from 93% to 98%. The results of the Wilcoxon signed rank test on the pretest-posttest data revealed that the temperature p = 0.002, heart rate frequency p = 0.001, and oxygen saturation p = 0.000. The increased physiological responses were still in the range of normal.Conclusion: The KC can maintain the stability of LBWB physiological responses. By that, it is recommended for parents to continue KC as a home-care for LBWB until the weight reached 2500 grams.